Opinion 2456: Family-group names based on Ortalis Merrem, 1786 (Aves, Cracidae): usage conserved by suppression of the family-group names based on Ortalis Fallén, 1810 (Insecta, Diptera) - ICZN (Bulletin of Zoological Nomenclature, 2020)
Under the plenary power, the International Commission on Zoological Nomenclature has conserved the family-group name Ortalidini Donegan, 2012 (Aves, Cracidae) with this spelling and authorship by suppressing all family-group names based on Ortalis Fallén, 1810 (Insecta, Diptera). As a result, Ortalidaini Donegan, 2012 is an incorrect original spelling, and Ortalisini David, 2014 is an unjustified emendation of Ortalidini Donegan, 2012.
Keywords: Nomenclature; taxonomy; ortalidaini; ortalidini; ortalini; ortalisini; chachalacas; ortaliscidae; ceroxydidae; family-group names; stem formation; homonymy; correct original spelling; English-French discrepancy